Mosquito-Borne Diseases: Social Representations of a University Community in Endemic Outbreaks - Sylvain Delouvée; Gail Moloney; Kathleen McColl; Grégory Lo Monaco (MDPI AG, 2021)
(1) Background: Studying social representations as lay theories allows for a better understanding of the common sense knowledge constructed around mosquito-borne diseases and the impact this may have on attitudes and behaviors. (2) Methods: A hierarchical evocation questionnaire was circulated through an Australian academic community and analyzed by prototypical analysis and correspondence factor analysis. (3) Results: Representational areas are regulated by participant age and whether or not they had contracted a mosquito-borne disease. (4) Conclusions: Collecting and understanding social representations has the potential to help social actors implement strategies that encourage people to access information and adopt behaviors in line with the scientific reality of the phenomenon, rather than limiting lay theories.